Building brand's value: Research on brand image, personality and identification - Chao Sen Wu; Tien-Tze Chen (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
The purpose of the study was to investigate and analyze the relationships among three research variables: brand Image, brand Identification and brand Personality. Standard surveys were administered to 1032 subjects who had knowledge of Volvo and the Volvo endorsement by Jeremy Lin and had purchased Volvo products. The study then used structural equation modeling to run path analysis. The results showed that: (1) brand image positively and significantly influenced brand identification, (2) brand personality positively and significantly influence brand identification, and (3) brand personality exhibited no mediating effect on the relationship between brand image and brand identification. The study found that enterprises should create high-value product attributes and brand personality to promote product value, and in doing this, enterprises can strengthen the overall brand image and enhance consumers' brand identification to help the sustainable management and competitiveness of the business.
Keywords: L83; O16; 330; Consumer; brand identification; brand image; brand personality; structural equation modeling (SEM)